2021
DOI: 10.3390/app11115248
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study for Assessing the Risk Reduction Using an Emergency Vehicle Equipped with a Micronized Water System for Contrasting the Fire Growth Phase in Road Tunnels

Abstract: We performed Computational Fluid Dynamics (CFD) modeling, and simulated a people evacuation process from a tunnel in the event of a fire, for evaluating the potentialities of using, as a temporary safety measure, an emergency vehicle equipped with a micronized water system for contrasting the fire growth phase. The structure investigated is a one-way road tunnel with only natural ventilation, and with a length less than 1000 m. The tunnel is assumed at present to be affected by refurbishment works for making i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The remaining heat absorbed by droplets came from tunnel surface cooling (9%) and radiation attenuation (18%). Ciro Caliendo [18] used CFD to simulate a particulate water system's fire-extinguishing effect on an emergency vehicle. The results showed that the particulate water system could significantly improve the environmental conditions of the escape path, which was related to changes in the temperature, radiant heat flux, and CO concentration.…”
Section: Related Workmentioning
confidence: 99%
“…The remaining heat absorbed by droplets came from tunnel surface cooling (9%) and radiation attenuation (18%). Ciro Caliendo [18] used CFD to simulate a particulate water system's fire-extinguishing effect on an emergency vehicle. The results showed that the particulate water system could significantly improve the environmental conditions of the escape path, which was related to changes in the temperature, radiant heat flux, and CO concentration.…”
Section: Related Workmentioning
confidence: 99%
“…This kind of measure was adopted by some Italian tunnel managers during the tunnels' modernization process to ensure an adequate level of safety. For instance, in the study of [28], a computational fluid dynamics (CFD) modeling is adopted to assess the effectiveness of emergency teams equipped with a micronized water system. Specifically, the process of evacuating users from a tunnel in the event of a fire was simulated to evaluate the use of an emergency vehicle equipped with a micronized water system to cope with a fire.…”
Section: Preparedness Mitigation Response Recoverymentioning
confidence: 99%
“…Moreover, as abovementioned, emergency teams can support tunnel users in their evacuation process by quickly providing useful information about the direction of the closest emergency exit to be reached [26]. In case of relevant events, thanks to the specific knowledge of the tunnel system, these teams can eventually support the intervention of other rescue teams (e.g., fire brigade) by providing detailed information about the evolution of the scenario and the infrastructure also through a continuous communication with the control center [5], [27], [28]. In another research, several tunnel fires were analyzed to estimate the response time and effectiveness of teams in controlling or extinguishing the fire.…”
Section: Resilience and Emergency Managementmentioning
confidence: 99%